Least Squares Fit of Definite Quadratic Forms by Convex Programming - Hartley, H. O.; Hocking, R. R.; Cooke, W. P. (Management Science, 1967)
This paper considers the problem of fitting a quadratic regression law subject to the condition that the fitted surface be convex (concave). A computational algorithm is described for determining the constrained regression coefficients using an existing non-linear programming algorithm. Some of the properties of the estimators are described.